Straight to yes asking with confidence and getting what you want - Imam, Haider (Gildan Audio, 2020)
Just having the best idea, product, service, presentation or proposal is no longer enough in these dizzyingly competitive times. Getting a commitment to action from your investors, leaders, customers or colleagues is vital. This book helps you become a master of gaining commitment to action by learning how to Ask. ' Based on sound psychological principles, Straight To Yes! offers tonnes of winning ways to make requests that get you to yes. Ruthlessly practical in style and full of immediately accessible, straightforward techniques you can try as soon as youve read about them. You can dip in and out of the book in 25 seconds before important Asks to refer to the single page you need for the step-by-step technique, or you can spend more time reading fascinating insights behind the art of Asking. ' Business matters. If we stumble at a crucial moment, all our hard work (and other peoples hard work too) can be undone. The stakes are high. This book gives you not only the tools to get it right but the confidence to ask bigger, ask wider, ask more often and even ask for the impossible. ' Table of Contents Part I: The Inner Game of Asking is all about preparing to make requests; overcoming inhibitors to making confident, successful requests (such as fear of rejection); introducing the seven keys that increase your chances of getting what you ask for.' ' Part II: Asking with Frames in Mind is all about external influences - how context and sequence influence peoples decisions, and how to frame your requests with this in mind. ' Part III: Asking with Tribes in Mind draws upon the best bits of social psychology to provide techniques that tap into values such as authority, status, consistency and trust. ' Part IV: Asking with the Brain in Mind draws upon neuroscientific evidence to show you how to tap into the inbuilt preferences in the brain and get a yes answer.
Downloadable audio file
Keywords: Business; Affaires; BUSINESS & ECONOMICS / Small Business; Downloadable audio books; Audiobooks; Livres audio